2018
DOI: 10.1107/s2052520618007321
|View full text |Cite
|
Sign up to set email alerts
|

Nollmotzite, Mg[UV(UVIO2)2O4F3]·4H2O, the first natural uranium oxide containing fluorine

Abstract: The twinned structure of the new uranium oxide mineral was refined from X-ray diffraction data and was found to contain fluorine and pentavalent uranium. The presence of pentavalent uranium is indicative of the reducing conditions under which the mineral formed. Nollmotzite is the first naturally occurring uranium oxide mineral that contains fluorine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
(34 reference statements)
3
5
0
Order By: Relevance
“…4) and bond-valence sums incident upon those sites (Tab. 5) are consistent with all Pb present as Pb 2+ , as is the case for all known Pb-containing uranyl-oxide hydroxy -hydrate minerals (Plášil 2018). According to site-scattering refinement results, some of the sites (Pb7 and Pb8) are considerably low-populated, <0.5.…”
Section: Refined Crystal Structure Of Wölsendorfitesupporting
confidence: 74%
See 4 more Smart Citations
“…4) and bond-valence sums incident upon those sites (Tab. 5) are consistent with all Pb present as Pb 2+ , as is the case for all known Pb-containing uranyl-oxide hydroxy -hydrate minerals (Plášil 2018). According to site-scattering refinement results, some of the sites (Pb7 and Pb8) are considerably low-populated, <0.5.…”
Section: Refined Crystal Structure Of Wölsendorfitesupporting
confidence: 74%
“…The third most complex UOH has to be newly considered wöl-sendorfite. This study revealed additional H 2 O sites, and both richetite and schoepite that had been considered in the past as far more complex turned out to be less-complex actually as they have been structurally revisited (Plášil 2017(Plášil , 2018. For comparison, the most complex mineral in Nature is the uranyl carbonate ewingite (Olds et al 2017b), Mg 8 Ca 8 (UO 2 ) 24 (CO 3 ) 30 O 4 (OH) 12 (H 2 O) 138 .…”
Section: Complexity Of Wölsendorfite In Comparison With Other Uohsmentioning
confidence: 76%
See 3 more Smart Citations